Implikasi Penerapan Metode Iqra’ Terhadap Pengenalan Cara Membaca Al-Qur’an Surat-Surat Pendek Kelas 1, 2 Dan 3 Di Madrasah Ibtidaiyyah Muhammadiyah Garut - Sulaiman, Husnan; Akbari, Aliqka Fatihah Nur (STAI Al-Musaddadiyah Garut, 2022)
The implementation of the Iqra' Method is a technique used in the approach to teaching and learning Quranic recitation. In teaching Quranic recitation, educators should meticulously adhere to the rules of Quranic recitation, including the identification of Arabic letters, proper pronunciation, and recognition of the forms of letters found in the Iqra' books and short Quranic chapters. Precision in pronunciation is crucial as any error can alter the meaning and interpretation of Quranic verses. At MI Muhammadiyah Garut, specifically in grades 1, 2, and 3, the Iqra' Method has been applied for the past seven years as part of a locally developed curriculum. This study aims to describe: (1) The implementation of the Iqra' Method in grades 1, 2, and 3 at MI Muhammadiyah Garut; (2) The introduction to reciting short Quranic chapters in grades 1, 2, and 3 at MI Muhammadiyah Garut; (3) The implications of the Iqra' Method on the introduction to Quranic recitation in grades 1, 2, and 3 at MI Muhammadiyah Garut. The research methodology employed is descriptive, with data collection techniques involving observation, interviews, and documentary analysis. Data analysis comprises data reduction, presentation, and conclusion drawing. The findings indicate that the implementation of the Iqra' Method at MI Muhammadiyah Garut significantly impacts students' ability to recite the Quran. Students demonstrate increased enthusiasm and proficiency in recognizing Arabic letters, thereby enhancing their ability to recite accurately according to established Quranic recitation principles. Keywords: Iqra' Method, Introduction to Quranic Recitation